2021
DOI: 10.1111/ijcp.14170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of the COVID‐19 pandemic on sleep disorders and nutrition in children

Abstract: Aims:The aim of the study was to evaluate the possible changes in sleep behavior and nutrition in children during the pandemic period.Methods: One hundred fourteen parents who accepted to participate in the study aged 18 and over and who had children between the ages of 6 and 16 were included in the study. A questionnaire was carried out after written consents were obtained.In the first part of the questionnaire, there were a total of 9 questions including socio-demographic information and nutritional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Moreover, a total score of global disturb might be obtained by the sum of subscales scores. Recently, several studies have investigated sleep disturbs in children during lockdown by SDSC questionnaire [ 3 , 16 19 ]. In addition to SDSC, we registered bedtime, hours of sleep, and use of smartphone around bedtime, use of electronic devices during the day and for e-learning was not investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a total score of global disturb might be obtained by the sum of subscales scores. Recently, several studies have investigated sleep disturbs in children during lockdown by SDSC questionnaire [ 3 , 16 19 ]. In addition to SDSC, we registered bedtime, hours of sleep, and use of smartphone around bedtime, use of electronic devices during the day and for e-learning was not investigated.…”
Section: Methodsmentioning
confidence: 99%
“…However, some research in Australia25 and Germany26 suggests physical activity increased 26. International studies also report an increase in adolescent sleep duration during lockdown periods,18 20 but higher prevalence of sleep problems, particularly among girls 27. Similarly, Australian adolescents perceived an increase in sleep difficulties and had increased sleep disturbance during the first lockdown 25.…”
mentioning
confidence: 99%
“…Emotional problems, along with gender, age, diet, device use, stress, and environment are factors that have been considered in studies as moderators of children’s sleep [ 11 , 13 , 15 , 33 , 34 , 35 , 37 ]. During confinement, girls were more likely to suffer from sleep disturbances [ 35 , 56 ], although previous research has indicated that this is truer in boys [ 56 ]. Younger boys spent more time in bed and went to sleep earlier [ 11 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, during confinement, children had more time available to themselves, and this has been unevenly distributed with increasing screen time and decreasing physical activity, both of which influence sleep [ 15 , 43 , 56 ]. A very high percentage of parents reported a change in children’s routines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%